Uji Aktivitas Antioksidan Formulasi Sediaan Krim Tabir Surya Ekstrak Etanol Biji Buah Durian (Durio Zibethiunus Murr) Dengan Menggunakan Metode DPPH - Aulia Mifta Huljanah (Jurnal Medika Nusantara, 2023)
Durian fruit seeds are seeds that contain chemical compounds, namely flavonoid compounds. Flavonoid compounds are active compounds that are include in the type of antioxidant intermedietes that act as antioxidants. The antioxidant mechanism of flavonoids is to capture free radicals and reactive oxygen species (ROS) directly, prevent the regeneration of ROS and can indirectly increase the activity of antioxidants and cellular antioxidant enzymes. This study aims to determine durian seed extract as a natural sunscreen and determine the formula for a good cream preparation. The method used in the study of durian seed extract (Durio Zibethiunus Murr) is the DPPH (1,1-diphenyl-2-pikrilhidrazil) method. Then the metod of extraction is using maceration with the differences in each formula for sunscreen cream namely 0%, 5%, 10% and 15%. The evaluations used in the study were organoleptic tests, homogeneity tests, pH tests, adhesion tests and spreadability tests. The result of this study indicate that the formulation of sunscreen cearm extract of durian fruit seeds (Durio Zibethiunus Murr) can be used as a sunscreen cream. The best sunscreen cream formulation is the 15% formula. The content of the antioxidant compounds ir more and meets the ultra value.